Humoral response to alpha gliadin as serological screening test for coeliac disease. - O'FARRELLY, CLIONA (My University, 1987)
The diagnostic value of measuring alpha gliadin antibodies in children with suspected coeliac disease has been evaluated prospectively. Jejunal biopsy and alpha gliadin antibody measurements were performed in 77 consecutive children who were being investigated for a suspected malabsorption syndrome. The typical small intestinal histological lesion of coeliac disease was found, and this diagnosis was subsequently confirmed clinically in 20 children. Raised IgG alpha gliadin antibody concentrations were found in 19 (95%). Fifty of 57 patients (88%) with a normal jejunal mucosa had normal alpha gliadin antibody concentrations. These results are similar to those previously reported in a prospective study of adult patients with coeliac disease and indicate that measurement of alpha gliadin antibody is a highly sensitive and specific screening test for childhood coeliac disease
PUBLISHED
Keywords: alpha gliadin antibodies; alpha gliadin antibodies; Immunology, Inflammation & Infection